2016
DOI: 10.1016/j.biopsycho.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Quantity language speakers show enhanced subcortical processing

Abstract: The complex auditory brainstem response (cABR) can reflect language-based plasticity in subcortical stages of auditory processing. It is sensitive to differences between language groups as well as stimulus properties, e.g. intensity or frequency. It is also sensitive to the synchronicity of the neural population stimulated by sound, which results in increased amplitude of wave V. Finnish is a full-fledged quantity language, in which word meaning is dependent upon duration of the vowels and consonants. Previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…It has been shown to reflect subcortical experience-based plasticity from auditory training and is affected by learning and language disorders [ 39 , 40 , 41 ]. It has previously been shown that wave V amplitude reflects enhanced duration processing at a subcortical level associated with quantity language experience [ 28 ], so the current study was interested in possible duration processing enhancement at the subcortical level due to musical expertise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to reflect subcortical experience-based plasticity from auditory training and is affected by learning and language disorders [ 39 , 40 , 41 ]. It has previously been shown that wave V amplitude reflects enhanced duration processing at a subcortical level associated with quantity language experience [ 28 ], so the current study was interested in possible duration processing enhancement at the subcortical level due to musical expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Language effects have been shown not only with tone languages but also quantity languages, like Finnish, which encode lexical duration. Previous studies have shown that native speakers exhibit enhanced perceptual, cortical, and duration processing at subcortical level [ 25 , 26 , 27 , 28 ]. The interaction of these effects with musical training, however, is more complex, and the effects of musical expertise within linguistic groups are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The main hypothesis for the brainstem data was motivated by recent research showing a group difference between Finnish speakers and German speakers in amplitude of the brainstem response, indicating an enhanced temporal synchrony (Dawson et al, 2016). In the previous work, simple duration discrimination data was unavailable, and comparisons were made between language groups, so it was not possible to test individual duration discrimination thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…Mandarin speakers, whose language has lexical tones, show more precise pitch representation in the brainstem and enhanced pitch contour detection in the auditory cortex (Xu et al, 2006; Chandrasekaran et al, 2009; Bidelman et al, 2011). Likewise, Finnish speakers, whose language has a durational (quantity) contrast between long and short in both vowels and consonants, show enhanced duration processing in the form of a smaller just noticeable difference (JND) for duration but not frequency (Tervaniemi et al, 2006), larger mismatch negativity (MMN) amplitude for duration in native speakers of Finnish compared to German speakers or Finnish second-language users (Nenonen et al, 2003; Tervaniemi et al, 2006), and more synchronized brainstem responses when compared to German speakers (Dawson et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Further, linguistic backgrounds in tonal and quantity languages had differential effects on perceptual auditory encoding in musicians. 1 The encoding was the most accurate in relation to the acoustic feature, which is most crucial in the native language of the participants ( Dawson et al. 2016 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%